Functions Modeling Change: A Preparation for Calculus, 5th Edition

Published by Wiley
ISBN 10: 1118583191
ISBN 13: 978-1-11858-319-7

Chapter 3 - Quadratic Functions - Exercises for Skills for Factoring - Page 135: 77



Work Step by Step

Solving the equation, we find: $$ n^2-2n-3=2n\left(n-3\right) \\ -n^2+4n-3=0 \\ n_{1,\:2}=\frac{-4\pm \sqrt{4^2-4\left(-1\right)\left(-3\right)}}{2\left(-1\right)} \\ n=1,\:n=3$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.